Relative potency factor approach enables the use of in vitro information for estimation of human effect factors for nanoparticle toxicity in life-cycle impact assessment. Issue 2 (7th February 2020) - Salieri, Beatrice; Kaiser, Jean-Pierre; Rösslein, Matthias; Nowack, Bernd; Hischier, Roland; Wick, Peter
Abstract: The major theme of the NRC report "Toxicity Testing in the Twenty-first Century" is to replace animal testing by using alternative in vitro methods. Therefore, it can be expected that in the future in vivo data will be replaced with in vitro data. Hence, there is a need for new strategies to make use of the increasing amount of in vitro data when developing human toxicological effect factors (HEF) to characterize the impact category of human toxicity in life cycle assessment (LCA). Here, we present a new approach for deriving HEF for manufactured nanomaterials (MNMs) based on the combined use of in vitro toxicity data and a relative potency factor (RPF) approach. In vitro toxicity tests with nano-CuO, nano-Ag and nano-ZnO and their corresponding ions were performed on THP-1, CaCo-2 and Hep-G2 cell lines. The ratio of the here calculated EC50 of the ionic form and the nanoform corresponds to the Relative Potency Factor (RPF). Using this approach, HEFs (case/kgintake ) for the aforementioned nanoparticles were obtained. Non-carcinogenic HEFs (case/kgintake) for exposure via ingestion of 5.9E-01, 7.5E-03 and 2.5 E-02 were calculated for nano-Ag, nano-CuO and nano-ZnO, respectively. The HEF values here proposed were compared with HEF values extrapolated from in vivo toxicity data reported in the literature. The here presented procedure is the most appropriate approximation currently available for using in vitro toxicity data on MNM for application in the field of LCIA.